Hepatitis B in persons infected with the human immunodeficiency virus in Porto-Novo – prevalence and associated factors. - WANVOEGBE, FINANGNON ARMAND; KPOSSOU, ABOUDOU RAÏMY; ATTINSOUNON, COSSI ANGELO; ZANNOU, DJIMON MARCEL; AGBODANDE, KOUESSI ANTHELME; AHOGBEHOSSOU, DONALD (My University, 2018)
Introduction: Approximately 5 to 25% of the 34 million people living with HIV (PLHIV) worldwide are co-infected with hepatitis B virus (HBV) or hepatitis C virus. The objective of this work was to determine the prevalence of HBsAg (Hepatitis B surface Antigen) in PLHIV at the University Hospital of Porto-Novo and to identify the factors associated with HIV-HBV co-infection. Methods: This was a descriptive and analytical crosssectional study covering the period from 1/ 2/ 2016 to 1/ 5/ 2016. PLHIV individuals with or without antiretroviral therapy (ARV) who were older than 15 years and had given their consent were included in the study. HBsAg was investigated by the DiaSpot One-Step Test Strip Rapid Test. Results: In the study participated 301 PLHIV individuals. The average age was 42 ± 10.3 years old. The age groups 35–45 (39.2%) and 25–35 (23.9%) were the most represented. Women (73.1%) were predominant. The main common risk factors related to HIV infection were unprotected sex (98%), multiple sexual partners (57.5%), circumcision outside hospital (66.7% of men), scarification (78.1%) and transfusion (17.6%). The prevalence of HBsAg was 14.3%. Factors associated with HIV-HBV co-infection were a history of liver disease and alanine aminotransferase levels more than twice the normal level. Conclusion: The prevalence of HBsAg was high in our PLHIV group. Local authorities in Benin should instigate measures to make HbsAg testing systematic during initial assessments of patients in order to adapt ARV treatment to each case.
Keywords: seroprevalence – HIV-HBV – co-infection – Benin